2013
DOI: 10.4049/jimmunol.1203535
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Play Crucial Roles in the Regulation of Mouse Collagen-Induced Arthritis

Abstract: Myeloid-derived suppressor cells (MDSCs) are of myeloid origin and are able to suppress T cell responses. The role of MDSCs in autoimmune diseases remains controversial, and little is known about the function of MDSCs in autoimmune arthritis. In this study, we clarify that MDSCs play crucial roles in the regulation of proinflammatory immune response in a collagen-induced arthritis (CIA) mouse model. MDSCs accumulated in the spleens of mice with CIA when arthritis severity peaked. These MDSCs inhibited the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
142
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(164 citation statements)
references
References 51 publications
17
142
3
1
Order By: Relevance
“…Although MDSCs have a deleterious role in cancer by inhibiting antitumor immunity (10)(11)(12)(13), it is possible that the cells have beneficial effects in autoimmunity by limiting T cell responses (8,14). In support of this possibility, recent studies have demonstrated that MDSCs accumulate in tissues with autoimmune diseases, including multiple sclerosis (15)(16)(17), inflammatory bowel disease (18,19), uveoretinitis (20), collagen-induced arthritis (21), and type 1 diabetes (22). However, the role of MDSCs in autoimmune diseases is not fully elucidated (14).…”
mentioning
confidence: 99%
“…Although MDSCs have a deleterious role in cancer by inhibiting antitumor immunity (10)(11)(12)(13), it is possible that the cells have beneficial effects in autoimmunity by limiting T cell responses (8,14). In support of this possibility, recent studies have demonstrated that MDSCs accumulate in tissues with autoimmune diseases, including multiple sclerosis (15)(16)(17), inflammatory bowel disease (18,19), uveoretinitis (20), collagen-induced arthritis (21), and type 1 diabetes (22). However, the role of MDSCs in autoimmune diseases is not fully elucidated (14).…”
mentioning
confidence: 99%
“…SCIenTIfIC RepoRts | (2018) 8:3753 | DOI:10.1038/s41598-018-21856-2 previous report 12 . The percentages of both M-MDSCs and G-MDSCs were also significantly higher in CIA mice on day 35 in both peripheral blood and spleen (Fig.…”
Section: Figure 1 Mdscs Repress Il-17 But Increase Foxp3 In Cd4+ T Cmentioning
confidence: 83%
“…Given the potent immuoregulatory activity of MDSCs, it could be expected that MDSCs could have therapeutic impact on RA. There have been discordant results regarding the effect of MDSCs on RA [12][13][14][15][16][17][18][19] . However, all the previous papers performed adoptive transfer of MDSCs in animal model of RA to verify whether the MDSCs had therapeutic effects on RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Накоп-лены четкие данные об их определяющей роли в подавлении активности иммунокомпетентных клеток при опухолевом росте [18]. Что касается аутоиммунной патологии, то определенно можно говорить о наличии их при данных заболеваниях, о возможности подавления развития аутоиммун-ных процессов с помощью введения этих клеток в эксперименте [12,13,17]. И в то же время име-ются противоречивые данные об изменении их количества при этих патологиях.…”
Section: клетки-супрессоры в иммунопатогенезеunclassified